The Bible And The Historian : Breaking the Silence about God in Biblical Studies - Minear, Paul S. (Paul Sevier), 1906-2007. (Nashville : Abingdon Press, 2002)
"This book is Prof. Minear's clarion for a return to authentic biblical theology. After more than fifty years of teaching and research, his message is still simple: biblical theology must pay attention to the emphases of the biblical writers. Contemporary biblical scholars, often best trained as historians, tend to dismiss those elements of the Bible most relevant to the faith of ancient and contemporary Christians. This book introduces contemporary students again to a study of the Bible with God at its heart."--Page 4 of cover.
Foreword / J. Louis Martyn -- Part I: Divine revelation and historical research -- The musician versus the grammarian: An early storm warning -- The transcendence of God and human historicity -- Christian eschatology and historical methodology -- Biblical ontology and ecclesiology -- Divine revelation and human knowledge -- Part II: The churches' memories of the Messiah -- The preparation (Matthew and Luke) -- The offense (Matthew) -- The covenant (Luke) -- The creative word (John) -- The resurrection and the life (John) -- Part III: The Messiah's presence with the churches -- The family (Hebrews) -- The homeland (Revelation) -- The bond (2 Corinthians) -- The peace (The New Testament) -- The hope (1 Peter) -- Part IV: The Messiah's gifts, the churches' gratitude -- The Spirit (Romans, Luke, Mark, and Revelation) -- The liberation (Galatians) -- The promise (John) -- The thanksgiving (The New Testament) -- The mission (Romans) -- The hymn (Philippians).
Includes bibliographical references and indexes.
Keywords: Biblical Theology. -- New Testament Interpretation and Criticism; New Testament Historical Theology -- Biblical Criticism Interpretation